2022
DOI: 10.1038/s41598-022-21434-7
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy prospectively predicts nocebo side-effects following COVID-19 vaccination

Abstract: The directionality between vaccine hesitancy and COVID-19 vaccine side-effects has not been hitherto examined. We hypothesized a nocebo effect, whereby vaccine hesitancy towards the second Pfizer vaccination dose predicts subsequent side-effects for a booster dose, beyond other effects. We expected these nocebo effects to be driven by (mis)information in males and prior experience in females. A representative sample of older adults (n = 756, mean age = 68.9 ± 3.43) were questioned in a typical cross-lagged des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…While nocebo effects are driven more by misinformation (verbal manipulation) in males, they are found to be driven by conditioning and previous experience in females [ 58 ]. This lagged effect is further documented by Hoffman and colleagues [ 59 ], who reported that COVID-19 vaccine side effects decreased across waves for males but increased for females. Accordingly, the association between wave one and wave two side effects (wave one following a second Pfizer dose, wave two after their booster) was more robust in females.…”
Section: Discussionsupporting
confidence: 61%
“…While nocebo effects are driven more by misinformation (verbal manipulation) in males, they are found to be driven by conditioning and previous experience in females [ 58 ]. This lagged effect is further documented by Hoffman and colleagues [ 59 ], who reported that COVID-19 vaccine side effects decreased across waves for males but increased for females. Accordingly, the association between wave one and wave two side effects (wave one following a second Pfizer dose, wave two after their booster) was more robust in females.…”
Section: Discussionsupporting
confidence: 61%
“…Available literature however accuses vector-based vaccines to be more frequently associated with (severe) neurological side effects [ 7 , 20 ]. On the other hand, mRNA-COVID‐19 vaccine side‐effects have been attributed to a nocebo component in association with vaccine hesitancy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some adverse reactions after vaccination possibly comprise a psychosomatic nocebo component that has been very poorly studied in individuals vaccinated against SARS-CoV-2 [ 14 ]. A study by Zhu et al showed that, after receiving a physiological solution, 37% of participants in the placebo group reported adverse events.…”
Section: Introductionmentioning
confidence: 99%